OPTIMIZING OXYGENATION: UNVEILING THE POTENTIAL OF INHALED NITRIC OXIDE IN THE MANAGEMENT OF EISENMENGER SYNDROME - Muhammad Triastuti; Anas Airlangga (The American Journal of Medical Sciences and Pharmaceutical Research, 2024)
Eisenmenger Syndrome poses a complex challenge in the realm of congenital heart diseases, characterized by pulmonary hypertension and shunting of blood. This paper delves into the potential of inhaled nitric oxide (iNO) as a therapeutic intervention for optimizing oxygenation in individuals with Eisenmenger Syndrome. Through a comprehensive review of existing literature, clinical studies, and case reports, this research explores the physiological mechanisms, safety profile, and efficacy of iNO in ameliorating hypoxemia and pulmonary vascular resistance associated with Eisenmenger Syndrome. The findings aim to contribute valuable insights to the evolving landscape of treatment options for this rare and intricate cardiovascular condition.